2006
DOI: 10.1002/ejlt.200500276
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐oxidant activity of Fe2+ in oxidation of cod phospholipids in liposomes

Abstract: This work examines how different factors such as temperature, amount of injected Fe 21, lipid concentration, pH, concentration of NaCl and concentration of dissolved oxygen influenced the lipid oxidation rate of liposomes made from cod phospholipids. The rate of lipid oxidation was measured by consumption of dissolved oxygen by liposomes in a closed vessel. The rate of oxygen consumption in liposomes was proportional to the concentration of iron and the lipid concentration in the assay mixture. The oxygen cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 30 publications
2
51
1
Order By: Relevance
“…Mabrouk and Dugan [23] explained the inhibition effect of NaCl on the oxygen uptake rate in emulsions by a decreased solubility of oxygen. However, in these studies, and as reported in our earlier studies, the oxygen uptake rate was constant at oxygen concentrations between 200 and 5 mM [14], and the reduction in the concentration of dissolved oxygen at 0.15 M NaCl is only 5% [24]. Mei et al [4] proposed that the ability of NaCl to decrease oxidation, at low iron concentration, could be due to the ability of NaCl to remove iron from the emulsion surface.…”
Section: Salts and Lipid Oxidationmentioning
confidence: 76%
See 3 more Smart Citations
“…Mabrouk and Dugan [23] explained the inhibition effect of NaCl on the oxygen uptake rate in emulsions by a decreased solubility of oxygen. However, in these studies, and as reported in our earlier studies, the oxygen uptake rate was constant at oxygen concentrations between 200 and 5 mM [14], and the reduction in the concentration of dissolved oxygen at 0.15 M NaCl is only 5% [24]. Mei et al [4] proposed that the ability of NaCl to decrease oxidation, at low iron concentration, could be due to the ability of NaCl to remove iron from the emulsion surface.…”
Section: Salts and Lipid Oxidationmentioning
confidence: 76%
“…Lipid classes were determined by thin-layer chromatography (TLC) [15] and detected by an Iatroscan TLC-flame ionisation detector (FID) system (TLC-FID analyser TH-10 MK-IV; Iatron Laboratories, Tokyo, Japan) as described by Mozuraityte et al [14]. Two replicate analyses were performed and the results were expressed in area% as the mean value.…”
Section: Raw Materials and Analytical Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The decrease in stability from 60 to 80 °C could be explained by the increase in lipid oxidation rate with increasing processing temperature (Carvajal et al, 2009;Mozuraityte et al, 2006). Lipid oxidation leads to the formation of peroxides that can decompose to lipid radicals and lead to formation of secondary products, thus shortening the induction period.…”
Section: Stability Of Produced Oilsmentioning
confidence: 94%